Compliance with IFRs: The case of risk disclosure practices in Egypt - Ekramy Mokhtar; Ali ElHaridy; Mohamed Mandour (Arab Economic and Business Journal, 2018)
This study investigates the factors underlying non-compliance with IFRSs in Egypt. Evidence for this research was collected and analyzed using semi-structured interviews with academics, auditors, financial managers and officers in the Capital Market Authority, the Egyptian Exchange and the Egyptian Institute of Directors. Findings highlight the negative impact procedures-oriented accounting education, insufficient role of the profession in monitoring the professional performance of auditors, lack of adequate continuing education, the focus of the Unified Accounting System on bookkeeping with little importance of disclosure. Finally, competitive disadvantage is a significant threat to the reporting practices of Egyptian companies.
Keywords: 330; Compliance; IFRSs; Disclosure; Risk; Accounting education; Enforcement mechanisms